STUDI TENTANG PARTISIPASI PESERTA DIDIK KELAS VIII DALAM KEGIATAN EKSTRAKURIKULER PADA SENI BUDAYA TARI DI MADRASAH TSANAWIAH NEGERI KOTA TERNATE - Nuraisyah Adam; Hasmawati Hasmawati (Jurnal Geocivic, 2018)
This research is motivated by an activity to foster the talents, interests and skills of students in the school, which are called extracurricular activities in cultural arts and dance. This study aims to determine the form of student participation in extracurricular activities in dance culture, as well as factors that inhibit the participation of students in extracurricular activities in dance culture. This study uses a type of descriptive qualitative research aimed at gaining a general understanding of social reality from a participant's perspective. The technique of collecting data through observation, interviews, and documentation. The data is analyzed using Data Reduction, Data Presentation, and Verification of Data and conclusions scientifically. The results of this study indicate the form of student participation in extracurricular activities in dance culture arts. The number of eighth grade students in the MTs Negeri Kota Ternate Ternate is 219 students. Only 50 students participated in extracurricular activities. This shows that the participation of students in extracurricular activities is very minimal. Because students are less interested and less like extracurricular activities in dance culture. Factors that hinder the participation of students in extracurricular activities in dance culture are mostly male students who feel inferior to participate in extracurricular activities in the field of dance culture, this is due to male students assume that extracurricular activities in dance culture are especially for female students. So that students who take extracurricular activities in the art of dance culture are mostly female students compared to male students. Keywords: extracurricular activities, dance culture, learners, participation